2022
DOI: 10.30595/pshms.v2i.247
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Quality of Life Quality of Adults with Coronary Artery Disease (CAD)

Abstract: Quality of Life is as a predictor of general wellbeing that is an important outcome in the treatment of any chronic disease. Impaired quality of life has increasingly become the most significant health outcome for CAD patients. The purpose of this study was to identify the predictor of quality of life of adults with CAD Patients. A descriptive cross-sectional study was conducted with sample of 125 participants of age between 35 to 64 years from RSUP. Dr. M. Djamil Hospital, Padang, West Sumatera, Indonesia. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
1
1
2
Order By: Relevance
“…In various Studies 23,24 it has been the men's scores were significantly higher than the females' in all four domains of QoL among cardiac disease, although such results were inconsistent with the present study. In the present study findings, age and gender did not statistically significant relationship with any of the study variables (QOL and its domain, medical adherence and overall satisfaction with health scores), consistent findings were also reported by Zuriati et al 19 in which age and gender were not associated with QOL.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In various Studies 23,24 it has been the men's scores were significantly higher than the females' in all four domains of QoL among cardiac disease, although such results were inconsistent with the present study. In the present study findings, age and gender did not statistically significant relationship with any of the study variables (QOL and its domain, medical adherence and overall satisfaction with health scores), consistent findings were also reported by Zuriati et al 19 in which age and gender were not associated with QOL.…”
Section: Discussionsupporting
confidence: 92%
“…A study done by Lee 18 , reported that adherence to lifestyle modification tended to be higher in females and those who were less educated and lifestyle medication factors such as a low salt diet, regular exercise, drinking alcohol and smoking cessation were associated with higher medical adherence, however in the present study, only level of physical activity was associated. A study done by Zuriati et al 19,20 reported that educational status, income and occupation were significantly associated with QOL but such findings were not reported by the present study, however, the domains of QOL (Physical, social and environmental) were associated with educational status which indicates that participants with a higher level of education were more likely to have a better quality of life in terms Physical, social and environmental domain. Present findings indicate that QOL was significantly associated with sociodemographic variables like marital status, this indicates that married people have a support system as a life partner, and consistent results were also reported by Zuriati et al 19 and Hung et al(2010) 21 and they concluded that the support system had a significant direct impact on quality of life and decreased the readmission rate among CAD patients.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations